Imaging and Spectral Fitting of Bright Gamma-Ray Sources with the COSI Balloon Payload - Jarred M. Roberts; Steven Boggs; Thomas Siegert; John A. Tomsick; Marco Ajello; Peter von Ballmoos; Jacqueline Beechert; Floriane Cangemi; Savitri Gallego; Pierre Jean; Chris Karwin; Carolyn Kierans; et al. (The Astrophysical Journal)
The Compton Spectrometer and Imager balloon payload (COSI-Balloon) is a wide field-of-view Compton gamma-ray telescope that operates in the 0.2–5 MeV bandpass. COSI-Balloon had a successful 46 day flight in 2016 during which the instrument observed the Crab Nebula, Cygnus X-1, and Centaurus A. Using the data collected by the COSI-Balloon instrument during this flight, we present the source flux extraction of signals from the variable balloon background environment and produce images of these background-dominated sources by performing Richardson–Lucy deconvolutions. We also present the spectra measured by the COSI-Balloon instrument, compare and combine them with measurements from other instruments, and fit the data. The Crab Nebula was observed by COSI-Balloon, and we obtain a measured flux in the energy band 325–480 keV of (4.5 ± 1.6) × 10 ^3 ph cm ^−2 s ^−1 . The model that best fits the COSI-Balloon data combined with measurements from NuSTAR and Swift-BAT is a broken power law with a measured photon index Γ = 2.20 ± 0.02 above the 43 keV break. Cygnus X-1 was also observed during this flight, and we obtain a measured flux of (1.4 ± 0.2) × 10 ^3 ph cm ^−2 s ^−1 in the same energy band and a best-fit result (including data from NuSTAR, Swift-BAT, and INTEGRAL/IBIS) was a cutoff power law with a high-energy cutoff energy of 138.3 ± 1.0 keV and a photon index of Γ = 1.358 ± 0.002. Finally, we present the measured spectrum of Centaurus A and our best model fit to a power law with a photon index of Γ = 1.73 ± 0.01.